Clinicopathological Profile of Chronic Myelomonocytic Leukemia Cases: An Experience from A Tertiary Care Center - Azeez, Nabeel; Somasundaram, Venkatesan; Sharma, Isha; Sharma, Sanjeevan; Malik, Ajay (Annals of Pathology and Laboratory Medicine, 2019)
Background: Chronic myelomonocytic leukemia (CMML) is a clonal hematological neoplasm with features of both myeloproliferation and myelodysplasia with an incidence 0.4 per lakh population. A number of prognostic risks scoring systems have attempted to predict survival and risk of CMML patients, like International Prognostic Scoring System (IPSS), the Spanish Score, the modified Bournemouth Score, the Dusseldorf Score and the MDAP Score. But no prognostic system has been widely accepted. More data from different regions are required to create a widely accepted working prognostic system for CMML. No case series on CMML has been published in literature from India in our knowledge. This article attempts to put to light the various clinicopathological parameters of CMML cases from India and the impact of these parameters on final outcome. Methods: All admitted patients in a tertiary center in western India, with a diagnosis of either a chronic myeloproliferative disease or a myelodysplastic disease over a period of 3 years (2015-2018) were evaluated, out of which nine(n=9) cases fulfilled the diagnostic criteria of CMML. All patients underwent peripheral blood examination, bone marrow aspirate, bone marrow biopsy and cytogenetic studies. Result: All patients (n=9) were between 50 and 80 years and most were males (n=8). Five patients presented with hepatosplenomegaly. Renal and liver function of one patient was deranged who had pleural effusion, ascites. Most patients (n=8) had total leukocyte count above 13000/cumm, while three had low platelet counts. Two out of three patients classified as CMML-II with increased blasts in peripheral blood and bone marrow had fatal outcomes. Patients whose karyotypes were available had normal karyotypes without any additional cytogenetic abnormalities. All were negative for JAK2 and BCR-ABL1. Conclusion: The study concluded that altered biochemical tests (LDH, LFT), blast percentage, CMML II, relative lymphocytosis and transformation to AML were associated with poor outcome.